Implementation of the Life Skills Curriculum in Shaping Students’ Character at De'green Camp High School, Tanjungpinang City - megawati, megawati (Lembaga Penelitian dan Pendidikan Mandala, 2023)
Life skills are abilities that are driven by individuals to be willing and brave to face the problems of life and life normally without feeling forced, then proactively and imaginatively seek and explore the solutions obtained. De Green Camp Islamic School from the Tujuh Pilar Utama foundation has opened the Admission of New Learners (PPDB) for De Green Camp Islamic High School in 2022. A high school with the main goal of